Density Functional Study of the Reaction Mechanism of Two Oxiimine Alcohol Formations and Their Novel Rearrangements. Issue 5 (17th May 2016) - Kaya, Yunus
Abstract : In this study, the reaction mechanisms of isonitrosoacetophenone (inapH) with ethanolamine (ea) and 1‐phenylethanolamine (pea) have been investigated theoretically using B3LYP/6‐311G(d, p) method to explain why the formation and unexpected rearrangement products occur or not occur. While the reaction between isonitrosoacetophenone (inapH) with ethanolamine gives oximine alcohol (Ib ), the reaction of 1‐phenylethanolamine with inapH results in the formation of oximine alcohol with a different substituent (Ia ) and amido alcohol (IIa ), which is the unexpected rearrangement product. The rearrangement driving forces of compounds fromIa toIIa are calculated as ca . 28 and 23 kJ/mol in the gas and EtOH phases, respectively. These driving forces have been calculated ca . 46 and 45 kJ/mol for the rearrangement of compoundIb to obtainIIb in the same phases, respectively. This high driving force shows that the compoundIIb cannot be obtained from rearrangement of compoundIb as described experimentally in the literature. In addition, as the DFT functionals poorly describe dispersion effects, dispersion correction for reaction heat and free‐energy barrier was estimated using the wB97X‐D/6‐311G(d, p). In general, the relative free energies of all molecules calculated from wB97XD method are lower than performed from B3LYP level. The changes of thermodynamic properties for all molecules with temperature ranging from 100 to 500 K have been obtained using the statistical thermodynamic method. Abstract :